Fertility considerations and the pediatric oncology patient - Raffoul, Lara; Capito, Carmen; Sarnacki, Sabine (Seminars in pediatric surgery, 2016)
Recent years have witnessed marked improvement in cytotoxic treatments with a parallel increase in patient survival. Despite efforts done to minimize long-term side effects of these treatment regimens, it is estimated that 40% of survivors of pediatric cancer will suffer from those. Some will be mild whereas others such as impaired fertility will be a heavy load on parents׳ expectations and patient׳s quality of life. Gonadal damage and severe loss of function is not a rare condition among children cured for cancer. Despite the young age of those patients, methods exist to try to reduce gonadal insult or to preserve gonadal function. Some of them are well studied and controlled; others are more experimental with encouraging results so far. This article aims to summarize all the procedures that can be offered to young patients treated for cancer in order to protect, as possible, their fertility potential.